Circulating LOXL2 Levels Reflect Severity of Intestinal Fibrosis and GALT CD4+ T Lymphocyte Depletion in Treated HIV Infection - Sophie Seang; Anoma Somasunderam; Maitreyee Nigalye; Ma Somsouk; Timoty W. Schacker; Joyce L. Sanchez; Peter W. Hunt; Netanya S. Utay; Jordan E. Lake (Pathogens and Immunity, 2017)
Background: Incomplete immune reconstitution may occur despite successful antiretroviral therapy (ART). Gut-associated lymphoid tissue (GALT) fibrosis may contribute via local CD4+ T lymphocyte depletion, intestinal barrier disruption, microbial translocation, and immune activation.